Civil engineering in French a guide to the language and practice of civil engineering in French-speaking countries - Paulus, A., 1948- (Thomas Telford, 1982)
This volume is designed for the engineer with some basic knowledge of French. The aim of the book is to familiarize the reader with the practices and working environment he will encounter in French-speaking countries, as well as vocabulary and the application of French in civil engineering.
Keywords: Civil engineering -- Dictionaries -- French.; elektronické knihy; electronic books